Challenges in diagnosis and management of delirium in Lewy body disease. (4th November 2022) - Richardson, Sarah; Lawson, Rachael A.; Price, Annabel; Taylor, John‐Paul
Abstract: Background: Delirium is an acute onset and fluctuating impairment of cognition, attention and arousal, often precipitated by acute illness. Lewy body disease (LBD) is an umbrella term for a range of clinical conditions, including Parkinson's disease dementia (PDD) and dementia with Lewy bodies (DLB). People living with LBD seem to be more susceptible to delirium than those with other subtypes of dementia. Aim: To describe the challenges in clinical diagnosis and management of LBD. Methods: A systematic review of published literature on diagnosis and management of delirium in LBD. Results: Delirium is particularly challenging to diagnose in LBD as many of the clinical characteristics which define delirium such as inattention, fluctuating arousal, complex visual hallucinations and delusions, are also common to LBD. Distinguishing delirium from LBD can be very difficult clinically especially in the prodromal stages. Both under and over diagnosis of delirium, and under and over treatment of the symptoms have the potential to compromise the care and safety of people with a diagnosed or undiagnosed LBD. Clinicians are currently working with an extremely limited set of evidence‐based management options for those with delirium in the context of a LBD diagnosis. For patients with LBD and their families this is an area of clinical practice that needs focused research.